Spatial distribution of pesticide use in Brazil: a strategy for Health Surveillance - Pignati, Wanderlei Antonio; Lima, Francco Antonio Neri de Souza E; Lara, Stephanie Sommerfeld de; Correa, Marcia Leopoldina Montanari; Barbosa, Jackson Rogério; Leão, Luís Henrique da Costa; Pignatti, Marta Gislene (Ciência & saude coletiva, 2017)
The intensive use of pesticides in Brazilian agriculture is a public health issue due to contamination of the environment, food and human health poisoning. The study aimed to show the spatial distribution of the planted area of agricultural crops, the use of pesticides and related health problems, as a Health Surveillance strategy. We obtained data from the planted area of 21 predominant crops, indicators of the consumption of pesticides per hectare for each crop and health problems. The amount of pesticides used in the Brazilian municipalities was spatially distributed and correlated with the incidence of pesticides poisoning: acute, sub-acute and chronic. There was a predominance of soybean, corn and sugar cane crops, which together accounted for 76% of the area planted in Brazil in 2015. Some 899 million liters of pesticides were sprayed in these crops, and Mato Grosso, Paraná and Rio Grande Sul used the largest quantities, respectively. The health problems showed positive and significant correlations with pesticide use. The methodological strategy facilitated the identification of priority municipalities for Health Surveillance and the development of intersectoral actions to prevent and mitigate the impacts of pesticides on health and the environment.